The scenographic, costumed chorus, agency and the performance of matter: A new materialist approach to costume. (1st October 2019) - Barbieri, Donatella; Crawley, Greer
This article presents the performativity of costume as generated through materially discursive iterative processes that embed meaning in the production itself through the analysis of the chorus costumes for the 2018 Opéra du Rhin production of Eugene Onegin. It argues that a new materialist approach can reveal the ethical concerns, around gender, toxic masculinity and compliance to reactionary social conventions, that lie at the core of this costuming of an opera chorus, particularly when perceived through the multiple forms that shape its distinct materializations over three successive acts. In addition, a focus on the agential actions of materials will draw attention to the work of the costume department, which to date has remained largely unaddressed by analytical approaches that are solely based on spectatorship, semiotics or phenomenological perspectives. Identifying the agential actions that materials perform enables the articulation of the costume specialist's response to the performativity of materials. Adopting a new materialist approach, 'costuming' is found to be an evolving and relational form that emerges from a complex process of meaning-making that addresses, through a distribution of agency, how materials connect to wider concerns.